‘PENGANTIN PESANAN’ SEBAGAI ARENA PERLAWANAN - Anggraini, Yayuk (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2020)
‘Pengantin pesanan’ or ‘kawin foto’ is a form of oppression and violence against women. This study did not refuse it, but it showed that the women of ‘pengantin pesanan’ did not always become the victims if: (1) violence and oppression faced by the women were not only ‘mail-order brides’ but also poverty, cultural violence, and unfair social structure; (2) the women keep fighting against the subjects who oppress them. The main focus of this study was the women’s effort to get out of the experienced oppression, i.e. the fight against poverty, the fight against cultural violence, the fight against Taiwanese and unfair social structure in their own villages. The writer believes that this study aims to be a self-criticism of the mainstream (feminist) discourse, so it needs an alternative approach by understanding the complexity of ‘pengantin pesanan’ which positions the women’s perception and (subjective) experience as the center of analysis, not discussing whether ‘pengantin pesanan’ is trafficking or not. The women’s subjectivity is formed by the discourse on “Women”, but not completely, because the women are basically controlled, but it does not mean that they cannot do anything since they still have some moving space or room for negotiating.